PHYTOCHEMICAL STUDY OF BACCHARIS DRACUNCULIFOLIA (ASTERACEAE) WITH ANTIOXIDANT POTENTIAL FOR THE DEVELOPMENT OF PHYTOCOSMETICS FORMULATION - Maria Rocha e Silva Crespo, Juliana; Teixeira Lazzari, Pamella; de Carvalho Ladeira, Rondinelli; Soares Crespo, Marcelo; Picanço Damian Resende, Sthepano (Health and Society, 2024)
This study addressed the development of a phytocosmetic with antioxidant appeal, using the extract of Baccharis dracunculifolia (Asteraceae) with therapeutic potential as the active ingredient. The research involved the phytochemical analysis of the plant, highlighting the presence of compounds such as alkaloids, flavonoids, and tannins, indicative of antioxidant activity. Baccharis dracunculifolia, known as “alecrim do campo,” was collected in the rural area of Muriaé, MG, and subjected to different extraction techniques to obtain hydroalcoholic and glycolic extracts. Phytochemical screening revealed the presence of phenols, tannins, saponins, and other compounds, crucial for the desired activity. Based on these results, a phytocosmetic gel with a low concentration of fatty components was formulated, aiming for efficacy and safety. The stability of the product was assessed under various conditions, and physicochemical parameters, such as pH and viscosity, were monitored. The phyto-cosmetic gel demonstrated stability throughout the study, maintaining its organoleptic and physicochemical characteristics. The final product composition included 2% of alcoholic extract of Baccharis dracunculifolia. This study contributes to the research on antioxidant phytocosmetics, highlighting the therapeutic potential of Baccharis dracunculifolia, but additional “in vivo” tests are required to validate its safety and efficacy in users.